Toward a digital One CGIAR: Strategic research on digital transformation in food, land, and water systems in a climate crisis - King, Brian; Devare, Medha; Overduin, Mathilde; Wong, Kelvin; Kropff, Wietske; Pérez, Sandra; Güereña, David T.; McDade, Marianne; Kruseman, Gideon K.; Reynolds, Matthew P.; Molero, Anabel; Sonder, Kai; et al. (CGIAR Platform for Big Data in Agriculture, 2021)
The global research consortium CGIAR is restructuring itself to build a more integrated global organization (“One CGIAR”) that fully leverages its strengths and refocuses its research strategy through 2030 in service of a renewed mission: End hunger—through science to transform food, land, and water systems in a climate crisis. The CGIAR Platform for Big Data in Agriculture led strategic research in support of this effort, looking into digital trends that have the potential to transform global agriculture in the coming years, the roles public-interest organizations should play in the digital agriculture landscape, and the capabilities CGIAR must have if it is to use data and digital technology to their full potential in the service of its mission.